Enhancing Embedded Data Security By Turns Cipher Block Chaining Mode Into Stream Cipher - Salah Mahdi Saleh (Engineering and Technology Journal, 2009)
In this paper, a secure data hiding method is introduced. It increases the security of embedded data through combining between the steganography and cryptography. First, the secrete message is divided into blocks with same size according to length of key stream that is generated using nonlinear key generator. This key is used to encrypt the first block in secret message using the stream cipher, whereas the other blocks are encrypted depending on the behavior of cipher block chaining (CBC) mode that turn on the stream cipher in order toguarantee no duplicated encrypted blocks. In our CBC mode the current ciphertext block will became a key stream to encrypt the next plaintext block, and so on. After encryption stage complete, the encrypted massage are embedded randomly in bmp image using LSB insertion method to increase the security.